Application Of Response Surface Methodology For Optimizing The Oxidative Stability Of Natural Ester Oil Using Mixed Antioxidants - Ab Ghani, Sharin; Muhamad, Nor Asiah; Zainuddin, Hidayat; Noorden, Zulkarnain Ahmad; Mohamad, Noraiham (IEEE, 2017)
Natural ester insulation (NEI) oils have been developed since the early 1990s due to the increasing environmental, health and safety concerns from the public. NEI oils are well-known for having high fire and flash points, great moisture tolerance, good biodegradability and non-toxicity. However, NEI oils also have several drawbacks compared to mineral insulation (MI) oils such as low oxidative stability, high viscosity, low pour point and low resistance towards lightning impulse. Previous researchers have discovered that the oxidative stability of NEI oils can be improved by the addition of mixed antioxidants. However, such studies are focused on only one criterion and they neglect the dielectric strength of the oils. On the other hand, the one-factor-at-a-time (OFAT) method is commonly used to determine the optimum concentration of mixed antioxidants and requires a large number of samples. In this study, response surface methodology (RSM) technique is used to determine the optimum concentration of mixed antioxidants which will enhance the oxidative stability of NEI oil. The dielectric strength of the NEI oil is evaluated based on the AC breakdown voltage (BdV). RSM is chosen in this study because it is capable of determining the optimum values of the parameters of interest, without the need for a large number of test runs which will incur high cost for experimentation. A regression model is developed in this study based on the AC breakdown voltage of the NEI oil, propyl gallate and citric acid antioxidant concentrations. The oxidative induction time (OIT) and partial discharge inception voltage (PDIV) are carried out to determine the effect of the oxidative stability and withstand voltage on the partial discharge, respectively. The results showed that there is enhancement in the oxidative stability and dielectric strength of NEI oil using the optimum concentrations of mixed antioxidants relative to the fresh NEI oil. It can be concluded that RSM is a feasible alternative to determine the optimum concentration of antioxidants for NEI oils, which in turn, helps improve the oxidative stability and dielectric strength of these oils.